Pharmacokinetic and Tissue Distribution Study of Solid Lipid Nanoparticles of Zidovudine in Rats - Shah Purvin; Parameswara Rao Vuddanda; Sanjay Kumar Singh; Achint Jain; Sanjay Singh (Journal of Nanotechnology)
Zidovudine-loaded solid lipid nanoparticles (AZT-SLNs) and zidovudine in solution were prepared and administered in rats. The aim of this research was to study whether the bioavailability of zidovudine can be improved by AZT-SLNs perorally to rats as compared to oral administration of zidovudine. Zidovudine was determined in plasma and tissues by reverse phase high performance liquid chromatography. The pharmacokinetic parameters of zidovudine were determined after peroral administration: area under curve of concentration versus time (AUC) for AZT-SLNs was 31.25% greater than AZT solution; meanwhile mean resident time (MRT) was found to be 1.83 times higher for AZT-SLNs than AZT solution. Elimination half life of zidovudine was also increased for SLN formulation. Tissue distribution pattern of zidovudine was changed in case of AZT-SLNs. AUC of zidovudine in brain and liver was found to be approximately 2.73 and 1.77 times higher in AZT-SLNs than AZT solution, respectively, indicating that AZT-SLNs could cross blood brain barrier. Distribution of zidovudine was approximately 0.95 and 0.86 times lesser in heart and kidney, respectively. It can be concluded from the study that oral administration of AZT-SLNs modifies the plasma pharmacokinetic parameters and biodistribution of zidovudine.